Non–fluorescent mutant of green fluorescent protein sheds light on the mechanism of chromophore formation. Issue 9 (20th April 2018) - Bartkiewicz, Małgorzata; Kazazić, Saša; Krasowska, Joanna; Clark, Patricia L.; Wielgus‐Kutrowska, Beata; Bzowska, Agnieszka
Abstract : The mechanism of green fluorescent protein (GFP) chromophore formation is still not clearly defined. Two mechanisms have been proposed: cyclisation–dehydration–oxidation (Mechanism A) and cyclisation–oxidation–dehydration (Mechanism B). To distinguish between these mechanisms, we generated a non–fluorescent mutant of GFP, S65T/G67A‐GFP. This mutant folds to a stable, native‐like structure but lacks fluorescence due to interruption of the chromophore maturation process. Mass spectrometric analysis of peptides derived from this mutant reveal that chromophore formation follows only mechanism A, but that the final oxidation reaction is suppressed. This result is unexpected within the pool of examined GFP mutants, since for the wild‐type GFP, there is strong support for mechanism B. Abstract :